Design and Construction of Water Turturity Monitoring Equipment and Automatic Water Pump - Tri Krisna, Rivaldo; Fitriani, Endah; Paramitha, Nina; Ariyandi, Tamsir (Universitas Nusa Putra, 2025)
The ever-increasing need for clean water requires innovation in water quality management and monitoring. This research aims to design and develop a water turbidity monitoring tool and an automatic water pump based on the Internet of Things (IoT) using the ESP32 microcontroller. The main objectives of this research include implementing ESP32 as the main controller, developing a system that can detect and monitor water turbidity levels in real-time using a turbidity sensor. The research results show that the designed tool is able to work well, with a measurement error rate of less than 5%, which shows high accuracy. The turbidity sensor and ultrasonic sensor work optimally, able to determine whether the water is clear or cloudy, and control the water pump automatically. The water pump will stop if the water level exceeds 32 cm or the water turbidity value exceeds 20 NTU. This system successfully meets the initial research objectives, offering an efficient and reliable solution for water quality management.